Fabrication of polypyrrole nanoparticles using microemulsion polymerization for diferent Py/APS/SDS molar ratios - Santim, Ricardo Hidalgo; de Aquino, Hermes Adolfo [UNESP]; Malmonge, José Antonio [UNESP] (Trans Tech Publications, 2016)
Polypyrrole nanoparticles (PPy) were synthesized by the chemical oxidative microemulsion of pyrrole (Py) monomer using ammonium persulfate (APS) as an oxidant agent and sodium dodecylsulfate (SDS) as a surfactant at 28°C and 0°C. Different Py:APS:SDS molar ratios were used, and the properties of the resulting material were examined by four-probe DC electrical conductivity, ultraviolet-visible-near infrared (UV-vis-Nir), and Fourier-transform infrared (FTIR) spectroscopies as well as field-emission scanning electron microscopy (FESEM). UV-vis-Nir and FTIR spectra show the formation of a polaron band owing to the doping of PPy by SDS. The electrical conductivity and morphology of PPy nanoparticles depend on the synthesis conditions. Electrical conductivity of ~95.3×10-3 S/cm was achieved for PPy synthesized at 0°C. For the same Py:APS:SDS molar ratio, the nanoparticle shape changed from cylindrical to spherical upon simply lowering the synthesis temperature.
Keywords: Microemulsion polymerization; Nanoparticles; Polypyrrole